Jñānamīmāṃsā: darśanasaṅgoṣṭhayāḥ lekhasaṅgrahaḥ - Gaṅgannā, Ji (Mānyatāprakāśanam, 2011)
Transcript of papers on mimamsa philosophy, presented at a seminar titled "Jātiyāya-ālocanācakram" organised by Rashtriya Sanskrit Sansthan, Srisadasiva Campus, Orissa, during 21-22 October 2011